3559 Mechanisms of sebaceous skin microbial community remodeling through microenvironment modulation. (27th March 2019) - McCoy, William Howard; Rosa, Bruce; Martin, John; Mitreva, Makedonka; Henderson, Jeffrey P.
Abstract : OBJECTIVES/SPECIFIC AIMS: To understand the mechanisms of how a non-antimicrobial can reshape a commensal microbe community to cure a ubiquitous human disease. METHODS/STUDY POPULATION: Whole genome sequencing of bacterial isolates, metabolomic investigations of previously collected skin microbe isolates from patients, and structural investigations of a protein from these skin microbes. RESULTS/ANTICIPATED RESULTS: Metabolic pathways associated with adaptation to a changing skin microenvironment, novel antimicrobial characterization, and a structural understanding of a novel nutrient acquisition protein. DISCUSSION/SIGNIFICANCE OF IMPACT: Multiple angles of this investigation are poised to improve current non-antimicrobial dermatologic treatments and they have the potential to impact microbe-related diseases in other human microenvironments.